The Strategy for Growing Economic Potential by Improving Financial Literacy using 4.0 Technology - Juhadi, J; Hamid, Nur; Saadah, Nuris; Aroyandini, Elvara Norma (Universitas Muhammadiyah Surakarta, 2023)
The Kragan coastal area has high economic potential. However, the economic potential in Kragan needs to be optimally managed. Most of the fisheries sector is still run traditionally. So there is dependence between small fishermen, who are still traditional, on prominent/modern investors. Many small fishermen are shackled by poverty in this case. Thus, it is essential to increase public knowledge regarding financial management in the fisheries sector so that the economy of traditional fishermen is no longer dependent on large/modern fishermen. The solution offered by researchers is to increase public financial literacy by utilizing technology 4.0. This technology is focused on community empowerment through product marketing. This study uses a qualitative method. Data collection techniques using interviews and observation. The research population is the people on the coast of Kragan. The research analysis uses a qualitative descriptive analysis. The results show that the financial literacy rate is still relatively low, around 58.2%. Most informants chose to use the old method, so there was an imbalance between small fishermen who used the traditional method and big/modern fishermen. While the results of the FGD show that technology 4.0 can help grow the Kragan people's economy by managing fishery products and increasing financial literacy.